Effects of sodium hypochlorite on some physiological and cytogenetical parameters in Allium cepa L. exposed to salt stress - Çavuşoğlu, Kürşat; Doğu, Fadime; Çavuşoğlu, Dilek (Bangladesh Journal of Botany, 2019)
The effects of sodium hypochlorite (NaClO) on the seed germination, seedling growth (radicle length, radicle number and fresh weight), mitotic activity and chromosomal aberrations of Allium cepa L. germinated under salt stress were studied. Salt stress considerably inhibited the seed germination and seedling growth of A. cepa. Furthermore, it markedly reduced the mitotic index in root tip meristems of the seeds and increased the number of chromosomal aberrations. Whereas, the detrimental effects of salt on the seed germination, seedling growth, mitotic activitiy and chromosomal aberrations were dramatically alleviated in varying degrees by NaClO application.